Central Serous Chorioretinopathy Mistaken for Tuberculous Choroiditis - Marina Papadia; Carl P Herbort (Journal of Ophthalmic & Vision Research, 2011)
Purpose: To report a patient erroneously diagnosed with tuberculous choroiditis who was accordingly treated with long term steroids which in turn, worsened the actual disease process that turned out to be central serous chorioretinopathy (CSC). Case Report: A 59-year-old Caucasian man developed a chorioretinal disease in his right eye in 1997. Having a positive tuberculin skin test, tuberculous chorioretinitis was suspected and antituberculous therapy was administered for 4 months. In 2005, visual symptoms in the same eye recurred and despite negative interferon gamma release assay, tuberculous choroiditis was considered as the diagnosis and the patient further received massive corticosteroid therapy along with antituberculous agents. Despite a deteriorating clinical picture, therapy was continued. Upon initial examination at our center, no sign of inflammation was observed and a diagnosis of CSC was made, consequently steroid therapy was terminated. Conclusion: In some chorioretinopathies, it is difficult to differentiate inflammatory from non-inflammatory causes. One should observe the course of the disease and question the initial diagnosis when no improvement or deterioration occurs despite therapy.